29 Out-of-hospital cardiac arrest in patients with psychiatric disorder – characteristics and outcomes. (16th April 2018) - Barcella, CA; Mohr, GH; Kragholm, K; Blanche, P; Wissenberg, M; Hansen, SM; Folke, F; Torp-Pedersen, C; Kessing, LV; Gislason, GH; Sondergaard, KB
Abstract : Aim: Survival after out-of-hospital cardiac arrest (OHCA) has increased in several countries following improvements in prehospital OHCA-management. We investigated overall and temporal changes in characteristics and outcomes in OHCA-patients with previous psychiatric disorder. Method: We identified adult patients with OHCA of presumed cardiac cause from the Danish Cardiac Arrest Registry from 2001 through 2014. Using multivariable logistic regression we calculated odds ratio (OR) for cardiopulmonary resuscitation (CPR), survival upon hospital arrival, 30 day and 1 year survival after OHCA in patients with and without a history of psychiatric disorder identified by discharge diagnosis up to 10 years before OHCA. Results: Of 28.955 OHCAs, 4037 (13.9%) had a known psychiatric disorder. Psychiatric patients were younger, less likely to have bystander-witnessed OHCA (44.1% vs 51%) and shockable heart rhythm (14.8% vs 27.1%), but same degree of arrest in private home (64.5% vs 64.8%) and estimated time interval to first-rhythm-analysis by EMS-crew (12 min) compared to non-psychiatric OHCA-patients. In fully-adjusted models, psychiatric patients had the same probability of receiving bystander CPR (OR 0.93 [95% confidence interval, 0.83–1.02]), but lower probability of survival upon hospital arrival, 30 day and 1 year survival: OR 0.79 [0.71–0.89], 0.54 [CI: 0.46 to 0.64] and 0.49 [0.41–0.59], respectively. Temporal trends showed that the gap in 30 day and 1 year survival between psychiatric and non-psychiatric OHCA-patients became evident after 2007. Conclusion: Survival following OHCA among psychiatric patients is considerably lower compared with non-psychiatric OHCA-patients and the gap seems to widen over time despite the recent efforts to improve OHCA-management. Conflict of interest: None Funding: None